Społeczne postrzeganie związków intymnych młodzieży. Analiza narracji adolescentek i adolescentów - Jankowiak , Barbara (Studia Edukacyjne, 2023)
Youth develop their competence to build intimate relationships during adolescence. The aim of this project is to explore what adolescents experience regarding the social perception of their intimate relationships. The method of data collection was an individual in-depth interview and the method of data analysis was conventional content analysis. The group of participants in the study consisted of 22 adolescents (12 girls and 10 boys), aged between 14 and 19 years, who had experienced at least one intimate relationship during adolescence lasting at least one month. Participants could currently be in an intimate relationship or be single. Content analysis identified four main categories: 1) “It’s not a relationship, it’s just fun”; 2) “It’s not true love”; 3) “It won’t last very long”; 4) “You’ll get behind in school because of it!”. The results confirm that teenagers face stereotypical beliefs about their relationships. The results indicate the need to raise public awareness of the role of intimate relationships in young people’s development and to support adolescents in this vital area of interpersonal functioning.